A Case of Giant Uterine Lipoleiomyoma Simulating Malignancy - Erbil Karaman; Numan Çim; Gülay Bulut; Gülhan Elçi; Esra Andıç; Mustafa Tekin; Ali Kolusarı (Case Reports in Obstetrics and Gynecology)
Introduction. Uterine leiomyoma is the most common benign pathology in women and lipoleiomyoma is an extremely rare and specific type of leiomyoma. Here, we report an unusual case of giant pedunculated subserous lipoleiomyoma misdiagnosed preoperatively as leiomyosarcoma. Case. A 45-year-old woman admitted to our gynecology outpatient clinic for complaints of abdominal distention, tiredness, and pelvic pain for the last 6 months. Sonography and abdominal magnetic resonance imaging (MRI) showed a giant semisolid mass that filled whole abdominal cavity from pelvis to subdiaphragmatic area. A primary diagnosis of uterine sarcoma or ovarian malignancy was made. On operation, total abdominal hysterectomy with a pedunculated mass of size 30 × 23 × 12 cm and weighing 5.4 kg and bilateral salpingo-oophorectomy were performed. The histopathology revealed a lipoleiomyoma with extensive cystic and fatty degeneration without any malignancy. Discussion. The diagnosis of leiomyoma is done usually with pelvic ultrasound but sometimes it is difficult to reach a correct diagnosis especially in cases of giant and pedunculated lipoleiomyoma that included fatty tissue which may mimick malignancy. Conclusion. Subserous pedunculated giant lipoleiomyoma should be kept in mind in the differential diagnosis of leiomyosarcoma or ovarian malignancy.